THE IMPACT OF COVID-19 ON CHANGES IN THE ADAPTIVE EXPECTATION INFLATION MODEL OF EMERGING MARKET COUNTRIES - Rusiadi, Rusiadi (International Proceeding of Law and Economic, 2020)
This study examines the impact of Covid-19 on changes in the model of adaptive expectation inflation in emerging markets. The data was collected by month from June 2019 to July 2020. The data analysis model uses simultaneous regression of 2TLS. The results prove that there is a change in the behavior of the cagan model, where inflation expectations can be detected from the value of money supply, G.D.P., interest rate, and Balance of Payment. The impact of Covid-19 changes the behavior of inflation expectations from buying behavior to waiting for action; this is based on the decrease in purchasing power and the decrease in foreign trade transactions of emerging market countries.